Arl1p is involved in transport of the GPI-anchored protein Gas1p from the late Golgi to the plasma membrane - Liu, Ya-Wen; Lee, Szu-Wei; Lee, Fang-Jen S (Journal of cell science, 2006)
The molecular mechanisms involved in the transport of GPI-anchored proteins from the trans-Golgi network (TGN) to the cell periphery have not been established. Arl1p is a member of the Arf-like protein (Arl) subfamily of small GTPases and is localized in the late Golgi. Although Arl1p is implicated in regulation of Golgi structure and function, no endogenous cargo protein that is regulated by Arl1p has been identified in yeast. In this study, we demonstrate that Arl1p is involved in the anterograde transport from the Golgi to the cell surface of the glycosylphosphatidylinositol (GPI)-anchored plasma-membrane-resident protein Gas1p, but not the cell-wall-localized GPI-anchored proteins Crh1p, Crh2p and Cwp1p, or non-GPI-anchored plasma membrane-protein Gap1p. We also show that regulators of Arl1p (Sys1p, Arl3p and Gcs1p) and an effector (Imh1p) all participate in the transport of Gas1p. Thus, we infer that the signaling cascade Sys1p-Arl3p-Arl1p-Imh1p specifically participates in the transport of a GPI-anchored protein from the late Golgi to the plasma membrane.